2022
DOI: 10.3389/fnume.2022.829138
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 Immunohistochemical Expression Level ≥70%, Bulky Presentation ≥7.5 cm, Meningeal Lymphomatosis, and Interim PET ΔSUVmax After 4 Treatment Cycles <71% as Parts of a Practical Scoring System to Predict Progression-Free Survival and Overall Survival in Diffuse Large B-Cell Lymphoma

Abstract: Currently, prognostic models in diffuse large B-cell lymphoma (DLBCL) fail to closely reflect patients' biological, clinical, and survival heterogeneity. We, therefore, assessed the impact of clinical, biological, immunohistochemical (IHC), baseline (0), and interim (after 2 and 4 treatment cycles) PET (PET0, PET2, and PET4) data not yet included in any scoring system on DLBCL outcome. The analysis was conducted on 89 previously untreated adult patients of the Finistere Observatory Cohort (O.Ly.Fin) with docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A high proliferation index (Ki67) is generally considered a negative prognostic marker in B‐cell lymphomas. A meta‐analysis, 43 RCT (Ki67 threshold 75% in subgroup with IPI 2–3) 44 and a couple of retrospective trials (different thresholds up to 85%) 45 , 46 demonstrated the significance of high Ki67 as a prognostic marker in rituximab treated DLBCL. We tried to use various thresholds and a continuous variable ( p = .5) to determine the possible prognostic significance but no correlation with survival characteristics was found in all comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…A high proliferation index (Ki67) is generally considered a negative prognostic marker in B‐cell lymphomas. A meta‐analysis, 43 RCT (Ki67 threshold 75% in subgroup with IPI 2–3) 44 and a couple of retrospective trials (different thresholds up to 85%) 45 , 46 demonstrated the significance of high Ki67 as a prognostic marker in rituximab treated DLBCL. We tried to use various thresholds and a continuous variable ( p = .5) to determine the possible prognostic significance but no correlation with survival characteristics was found in all comparisons.…”
Section: Discussionmentioning
confidence: 99%